Comparing Effectiveness of New Training Program of Local Trainers of Community-Based Rehabilitation Program with the Current Program: A Knowledge, Attitude and Skills Study - Mohsen Iravani; Nikta Hatami-Zade; Ahmad Fotouhi; Samaneh Hossein-Zadeh (University of Social Welfare and Rehabilitation Sciences, 2011)
Objective: This research aimed at comparison effects of a new and current "training program for community rehabilitation workers of Community Based Rehabilitation", in enhancing their knowledge, attitude and skills. Materials & Methods: In this experimental field trial, a total number of 34 newly engaged local trainers in Lorestan province were divided randomly in two (16 and 18 peoples)interventional groups based on geographical location of their work places Teaching methods were roll playing, problem solving, and learning by doing in new program and the booklets were revised in terms of fluency and a guideline booklet for trainers were added in this program but the teaching method was reading booklets and demonstration of the skills in current program. Knowledge, Attitude and Skills of trainees assessed just before and after the training course based on the material which were used for the training course. K.A.P. changes of two groups were compared by independent t-test, Mann Whitney, Wilcoxon & Chi square. Results: Mean knowledge and skills scores increments were remarkably more significant after attending new course than after passing the current course (P<0.001) and more rehabilitation workers who attending new course use practical guides in addition to verbal instructions to train disabled people and their families (P=0.028). There were no significant differences in attitude changes among the two groups. Conclusion: As trainees learned more by means of the new training course and the two courses were not so different in the resource allocation, substituting the new method to the current one should get consideration.